The Relationship Between Maternal Characteristics and Socioeconomic Factors and the Incidence of Stunting Among Children Under Five in Palembik Village - Rafi’i, Ahmat; Sari, Apriani Susmita; Ririnsahawaitun (Bantayang Omni Cendekia, 2025)
Background: Stunting is a chronic form of malnutrition caused by prolonged inadequate nutritional intake, leading to impaired growth in children. This condition results in a child’s height being significantly shorter than the standard for their age. The impact of stunting can last a lifetime, affecting cognitive, motor, and verbal development, and may extend to the next generation. Objective: This study aimed to examine the relationship between maternal characteristics and socioeconomic factors with the incidence of stunting among children under five in Palembik Village, within the working area of the Darek Health Center, Southwest Praya District. Methods: This was an analytical study using a cross-sectional design to assess the association between independent variables (maternal characteristics and socioeconomic factors) and the dependent variable (stunting incidence). Data were analyzed using the Chi-square test. Results: Significant relationships were found between several maternal and socioeconomic factors with the incidence of stunting. Maternal age was significantly associated with stunting (p = 0.001), as was maternal height (p = 0.000). Maternal education also showed a significant association (p = 0.002). Among socioeconomic variables, father's education (p = 0.002), father's occupation (p = 0.001), mother's occupation (p = 0.000), and family income (p = 0.000) were all significantly related to stunting incidence. Conclusion: Maternal characteristics including age, height, and education as well as socioeconomic factors such as parental education, parental occupation, and family income, are significantly associated with the incidence of stunting in Palembik Village, Darek Health Center area, Southwest Praya District.